Потенциал иронии в творчестве Людмилы Петрушевской (на примере романа Нас украли. История преступлений) - Брюханова, Юлия (Studia Rossica Posnaniensia, 2020)
Many researchers of Lyudmila Petrushevskaya’s works draw attention to the irony which is the significant element of her prose, drama and poetry. It is important that the ironic principle manifests itself not only as an artistic technique but also as a philosophical aspect. Irony demonstrates the ambivalence of reality. On the one hand, it ridicules and profanes everything. On the other hand, irony gives the certitude of the ontological status of reality. We can see a good example of this function of irony in the novel Nas ukrali. Istoriya prestupleniy (2017). This novel shows the common features of Petrushevskaya’s works – the unity of ironic potential and language. In this case, language is not only the style but first of all the ontological element. This is why the language becomes almost a character in Petrushevskaya’s novel. Irony opens the vital potential of the linguistic personality. As a result, one of the heroes imitates foreign speech but doesn’t speak a foreign language. Irony also helps to reveal the ambivalent nature of life. It shows that our “umora” in Sanskrit and in ancient Indian is “humour” and “death”. So, the game and profanity not only reduce the status of the hero, the image, or the reader’s expectations but, first of all, fill the gap between words, ideas, feelings, and people.